Application of Zn-containing foliar fertilisers for recovery of the grain productivity potential of Zn-deficient maize plants - Krasimir Ivanov; Andon Vasilev; Anyo Mitkov; Nguyen Nguyen; Tonyo Tonev (Italian Journal of Agronomy, 2021)
Highlights - The application of foliar fertilisers is extremely suitable as the possibility of much faster zinc absorption than from the soil. - Zn-fertilisation of maize plants during the initial growth stages plays a decisive role in the formation of the reproductive organs of maize. - Foliar zinc fertilisers can entirely recover the physiological performance of plants grown under conditions of zinc deficiency.